METHODOLOGICAL APPROACHES TO ASSESSING THE ADAPTIVE POTENTIAL OF INTRODUCED GENOTYPES OF OCIMUM BASILICUM L. IN THE CONDITIONS OF THE SURKHAN-DARYA REGION (Universal International Scientific Journal, 2026)
The paper examines the theoretical and methodological aspects of studying thephysiological and biochemical resilience of foreign basil (Ocimum basilicum L.) genotypes to thenatural factors of the Surkhandarya region. The necessity of a comprehensive analysis of photosyntheticpigments and essential oil composition is substantiated for the selection of promising forms for theperfume industry.
Keywords: Ocimum basilicum; introduction; adaptation